Currency Crisis: Where Do We Go From Here? - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 1999)
This paper reviews the arguments for and against the imposition of capital controls in the Philippines and discusses the liberalization process undertaken by the authorities since the 1980s. The view espoused by this paper is that there is no need to impose selective capital control in the Philippines similar to that of Chile. However, to make the country less vulnerable to a currency crisis similar to that of the Southeast Asian currency crisis, the paper recommends three major measures: adoption of a flexible exchange rate; improvement of corporate governance; and strengthening of the banking system by improving prudential regulations to make it resilient in the face of sudden changes in investors' confidence.
Keywords: 330; Asian financial crisis; capital controls